Evaluasi Penerapan Sistem Informasi Smart Prodi dengan Pendekatan Delone Mclean dan Framework Cobit 5: (Studi Kasus: Sistem Penjadwalan Perkuliahan STMIK Amikom Purwokerto) - Tarwoto Tarwoto; Adam Prayogo Kuncoro (Universitas Bumigora, 2019)
Implementation of Information Systems used to improve the quality of service in the field of education at STMIK Amikom Purwokerto, the increasing problems in STMIK Amikom Purwokerto have not yet had a difference in terms of information systems to increase the system's prosperity. The method used is descriptive method using quantitative. The concept of this study uses the theory of DeLone and McLean combined with the COBIT 5 Framework which consists of 6 indicators including system quality, information, services, users, user satisfaction and net benefits. The results of this study are information systems that have been quite good and successful in the range of 0.80 the highest value of system quality, this explains about system users who have been carried out as daily activities to help use the operational process. The lowest value is service quality (0.50). This explains the quality of service received well needs improvement. And found some services that are less good and between good variables. Benefits of users, found to be related between information system development and information system maturity level (H0 rejected), but opposed not too strong or significant (0.38).